Executive Function Skills and Classroom Behaviors of U.S. Prekindergartners With Special Needs - Nesbitt, Kimberly T.; Farran, Dale C. (Frontiers in Education, 2022)
This study explores the executive function (EF) skills in a sample of four-year-old children all enrolled in inclusive prekindergarten (pre-k) classrooms. We compare the EF skills and important classroom behaviors of children with and without identified special needs as well as a sample of English language learners (ELL) in the same. Identification of special needs and ELL status were examined as these factors have previously been shown to be associated with young children’s EF skills. Compared to their classroom peers, children with identified special needs not only began the year with lower EF skills but made gains over the school year, a similar pattern was observed for children identified as ELL. Compared to their peers, children with identified special needs were observed as engaging in lower levels of involvement, sequential behaviors, and social learning interactions and higher levels of unoccupied and disruptive behaviors, a pattern that was also found for children’s entering EF skills (e.g., lower entering EF scores associated with lower levels of involvement). Lastly, children’s classroom behaviors differed across teacher-directed and children-directed learning with levels of level of involvement and social-learning interactions higher for child-directed learning and sequential behaviors higher in teacher-directed learning, a pattern that held across all groups of children.